Implementation of Solar Panels as an Energy Source for Automatic Fish Feed Machine Control Systems (Universitas Negeri Semarang, 2021)
Feed is the main need for fish consumption, feeding is sometimes a problem for breeders. An automatic fish feed machine with Arduino control via an android phone's Bluetooth signal as the communication method, equipped with an alarm indicating the condition of the feed is running out is the best solution. The automatic feed machine is placed in a pond outside the house so that solar energy can be absorbed by solar panels as a source of electrical energy for the machine and battery charger. Backup power when it's cloudy or at night and the machine doesn't need a state electricity company power source. The implementation of a 2.5 Wp solar panel and a 3000 mAh battery in this automatic fish feed machine is needed to simplify the daily feeding process. The result of this research is the maximum distance of control via an Android phone is 60 meters without obstructions and 30 meters with obstacles. When the battery voltage is 8 volts, the solar charger controller automatically cuts off the supply to the load to avoid a battery voltage drop. When the battery voltage rises to 10 volts, the load is activated again. From full 12.2-volt battery voltage to 8-volt drop it takes 6 hours and the load is automatically disconnected, 1.5 hours is needed for the battery to be re-charged by solar panels when the weather conditions are sunny and the load is active again.